Prevalence and predictors of malnutrition in elderly Chinese adults: results from the China Health and Retirement Longitudinal Study. Issue 17 (4th October 2018) - Wei, Jun-Min; Li, Shirley; Claytor, Ling; Partridge, Jamie; Goates, Scott
Abstract: Objective: China has the largest population of elderly citizens in the world, with 177 million adults aged 60 years or older. However, no national estimate of malnutrition in elderly Chinese adults exists. We estimated the prevalence and predictors of malnutrition in this population. Design: Data from the second wave of the Chinese Health and Retirement Longitudinal Study (CHARLS) include interview and biomarker data for 6450 subjects aged 60 years or older from 448 different communities in twenty-eight provinces, allowing for nationally representative results. Malnutrition was identified based on the ESPEN (European Society of Parenteral and Enteral Nutrition and Metabolism) criteria. We used multivariable regression to investigate the predictors of malnutrition, including demographic factors, marital status, self-reported health status, self-reported standard of living, health insurance status and education. Setting: China. Subjects: Community-dwelling Chinese adults aged 60 years or older. Results: The prevalence of malnutrition in elderly Chinese adults was 12·6 %. Malnutrition was most common among those who were older (OR=1·09; 95 % CI 1·07, 1·10), male (OR=1·41; 95 % CI 1·10, 1·79), lived in rural areas ( v . urban: OR=0·75; 95 % CI 0·57, 1·00) or lacked health insurance ( P <0·01). Conclusions: The burden of malnutrition on elderly Chinese adults is significant. Based on current population estimates, up to 20 million are malnourished. Malnutrition is strongly associated with demographic factors, shows a trend to association with health status and is not strongly associated with standard of living or education. A coordinated effort is needed to address malnutrition in this population.